Stroke types and management - Alrabghi, Lujain; Alnemari, Raghad; Aloteebi, Rawan; Alshammari, Hamad; Ayyad, Mustafa; Al Ibrahim, Mohammed; Alotayfi, Mohsen; Bugshan, Turki; Alfaifi, Abdullah; Aljuwayd, Hussain (International Journal Of Community Medicine And Public Health, 2018)
Strokes are a leading cause of morbidity and mortality across the world, in fact the third leading cause after heart diseases and cancer. Additionally, among the survivors of stroke, one-third suffers from permanent disabilities. Strokes can be classified broadly as ischemic and hemorrhagic, which account for 80% and 20% of total respectively. The prognosis of cerebrovascular accidents depends on quick diagnosis of the type, followed by appropriate and fast management. We conducted this review using a comprehensive search of MEDLINE, PubMed and EMBASE, from January 1982 to March 2017. The following search terms were used: stroke, cerebrovascular accidents, ischemic stroke, hemorrhagic stroke, stroke types, management of stroke, rehabilitation, CVA prevention. The most critical part about approaching a stroke patient is to identify the type of stroke, whether hemorrhagic or ischemic, as each type requires a different guideline of management. Also, time is the key in preserving neuronal function and preventing further damage. At the same time, the general population must be educated about methods of preventing stroke by making positive lifestyle changes.